Kūrybinio eksperimento sampratos architektūroje - Grunskis, Tomas (Journal of Architecture and Urbanism, 2011)
Understanding the concept of creative experiment in architectureWhile analysing creative experiments in architecture, one finds a number of different phenomena and examples, not so easy to discuss in a more or less systematic way. These phenomena and results, in one or another way related to experimental architecture, can hardly be defined by a single category and, as shown by the history of architecture, have become one of its driving forces contributing to the development of architecture in the course of time.The issue of the concepts of architectural experimentation on the whole is important and urgent in two aspects. First of all, such concepts are used in attempting to formulate basic architectural and cultural declarations, consequentially applied in forming and proclaiming different political creeds (usual practice of international architectural biennales and expo exhibitions). Secondly, their cultural value is of key importance too, as the ideas and thoughts expressed through the experimental creation often convey social aspects and states, also the idea, how architecture is understood during a specific period of time and the role given to it by society. Finally, as architecture is a language used by society to convey its socio-cultural status and values, the experimental architectural creation can be significant, although often ignored, in architectural practice.The most outstanding examples of architectural experiments confirm that architecture as artistic creation has long ago gained certain features of a cultural phenomenon, which eventually has become closely connected to society. Thus the area of culture and forms of its expression has becoming more and more relevant and significant to architectural experimentation.Although artistic and scientific experiments have certain similarities within contemporary discourse of architectural practices, they still differ a lot in the aspects of their backgrounds, processes and even results. But still, the interdisciplinary aspect, common to contemporary artistic experimentation, draws art and science closer together. Fairly often, peculiar new forms of art borrow scientific data or ideas interpreting, expressing and using them effectively to make pure art. The concept of architectural experimentation still does not exist as an integral concept. Only a few general features and attributes can be named as helping to define the architectural phenomenon as an experimental one. These are: (a) the idealistic trend and (b) very active element of motivation.It is also noteworthy that looking retrospectively, within different epochs the architectural experimentation had different relationship with other arts. The discussed in the article experimental practices of architecture in the 1950-ies – 1970-ies accumulated and effectively operated the languages of other visual – and not only – arts. Although, at the same time it should be admitted that they did not have the same close relationship to traditional, fundamental arts, such as sculpture and painting. So does the contemporary, the 21st century, architectural experimentation – it no longer has closer connection to traditional arts. Although it has to be admitted that the most recent, media-related arts influence experimental architecture on the levels of its forms as well as concepts.In general, the architectural creation at the beginning of the 21st century (both building architecture and urban planning) is getting more and more social. The experiment in such creation is less artistic or valuable as pure art in the traditional sense. Fewer experiments are made on the form only, but rather on the process itself and then – the form. Although the most innovative architectural images being developed and declared are getting more abstract and universal, they are easier to implement than before (due to the most advanced technologies). So, it is not so simple to draw a dividing line between purely idealistic and realistic experimental architecture, because what was just a vision not so long ago, today can be easily realized. Does it mean that experiments have become more social and less creative? Probably, not. Most likely, it’s because creativity has become transformable and gained new ways of expression.Article in Lithuanian.Santrauka. Straipsnyje analizuojamos esminės kūrybinio eksperimento sampratos architektūroje. Apžvelgiami pagrindiniai mokslinio ir meninio eksperimento principai, konceptai juos charakterizuojant bei lyginant tarpinternatvyje, detalizuojant tiek esminius skirtumus, tiek ir logines sąsajas tarp vienų ir kitų. Taip pat tekste plačiai analizuojamas kūrybinio eksperimento reiškinys architektūroje, aptariant ir mokslinės, ir meninės sričių įtakas jam, jo specifikas ir ypatumus.Reikšminiai žodžiai: eksperimentinė architektūra, kūrybinis eksperimentas, samprata.First Publish Online: 22 May 2013